Kidney organ donation: developing family practice initiatives to reverse inertia - Morgan Myfanwy; Stavroulaki Emilia; Symvoulakis Emmanouil K; Jones Roger (BMC Health Services Research, 2010)
Abstract Background Kidney transplantation is associated with greater long term survival rates and improved quality of life compared with dialysis. Continuous growth in the number of patients with kidney failure has not been matched by an increase in the availability of kidneys for transplantation. This leads to long waiting lists, higher treatment costs and negative health outcomes. Discussion Misunderstandings, public uncertainty and issues of trust in the medical system, that limit willingness to be registered as a potential donor, could be addressed by community dissemination of information and new family practice initiatives that respond to individuals' personal beliefs and concerns regarding organ donation and transplantation. Summary Tackling both personal and public inertia on organ donation is important for any community oriented kidney donation campaign.